PENGARUH ISOMETRIC HANDGRIP EXERCISE TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Hariyadi; Elen Ayu Ananda Prianita; Rela Hastuti; Sri Suhartiningsih (Jurnal Biogenerasi, 2026)
Hypertension or high blood pressure is one of the main health problems in the elderly that risks reducing the quality of life and increasing morbidity and mortality. Hypertension management efforts can be done pharmacologically and non-pharmacologically, one of which is by doing isometric handgrip exercise. This study aims to determine the effect of isometric handgrip exercise and its frequency on changes in blood pressure in elderly people with hypertension in X Village, Madiun Regency. This type of research uses a pre-experimental design with a one-group pretest-posttest design approach. The population of this study was elderly people with hypertension in X Village, Madiun Regency. The sample amounted to 18 respondents selected using a simple random sampling technique. Data were collected by measuring blood pressure before and after being given isometric handgrip exercise intervention for 5 consecutive days, then analyzed using the Wilcoxon signed rank test. The results showed that the average systolic blood pressure before the intervention was 151.67 mmHg and after the intervention became 133.33 mmHg, while the average diastolic blood pressure before the intervention was 91.67 mmHg and after the intervention became 77.78 mmHg. The results of the Wilcoxon test obtained a ρ-value = 0.000 (p < 0.05), which means there is a significant effect of isometric handgrip exercise on changes in blood pressure in elderly people with hypertension. This study shows that isometric handgrip exercise is effective in lowering blood pressure in elderly people with hypertension. This exercise can be used as a simple, safe, inexpensive, and easy to do non-pharmacological intervention independently at home.